NK cells in children with acute lymphoblastic leukemia and non-Hodgkin lymphoma after cessation of intensive chemotherapy - Jarosz, M; Hak, L; Wieckiewicz, J; Balcerska, A; Mysliwska, J (Termedia Publishing House Ltd., 2009)
Intensive, combination chemotherapy for malignant diseases causes a profound immunosuppression, which persists for the whole treatment period and after its completion. Impairment of the NK cells status may increase the risk of severe, disseminated infections and cancer. The aim of the study was the investigation of recovery of NK cells after cessation of intensive chemotherapy in children with acute lymphoblastic leukemia (ALL) and non-Hodgkin lymphoma (NHL). The number of CD3 - CD16+CD56+ cells in peripheral blood and NK cell cytotoxic activity were assessed in 23 children with ALL and 7 children with NHL at 2 weeks and 12 months after the cessation of intensive chemotherapy and in 15 healthy subjects. Absolute leukocyte, lymphocyte and NK cell counts and the percentage of NK cells in children with ALL were significantly lower than in control subjects both at 2 weeks and 12 months after intensive treatment. Additionally, the absolute numbers of leukocytes and lymphocytes decreased significantly after 12 months of observations in comparison to the initial time-point. In children with non-Hodgkin lymphoma at 2 weeks and 12 months after intensive treatment only absolute lymphocyte counts were significantly lower than values in healthy children. The absolute number, the percentage and cytotoxic activity of NK cells were comparable with values in the control group both at the initial and at the last time-point. The occurrence of infections during the 12 months of observations in patients with ALL were higher than in children with NHL and as many as eight of them were hospitalized because of severe infections. The differences between the ALL and NHL patients may be connected with the milder immunosuppressive effect of chemotherapy in the non-Hodgkin lymphoma since the children recovered from acute lymphoblastic leukemia remain with persistent defect of NK cells. It is then recommended that ALL children should be supervised with respect to an increased susceptibility to infections.